2016
DOI: 10.1108/jsbed-10-2013-0159
|View full text |Cite
|
Sign up to set email alerts
|

Internationalisation of Central and Eastern European small firms

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 54 publications
(99 reference statements)
1
35
0
2
Order By: Relevance
“…Furthermore, relational resources may facilitate access to different types of resources, including political influence, reputation, and even emotional support (Oh et al, 2006). Recent evidence from Romania acknowledged that both social and business networks represented the most important and reliable resource for SMEs' internationalisation (Stoian et al, 2016). Equally, evidence from Norway and Ireland showed that networks played an important role in increase speed of internationalisation (Langseth et al, 2016).…”
Section: Smes' Relationships and Export Performance: A Network-based mentioning
confidence: 99%
“…Furthermore, relational resources may facilitate access to different types of resources, including political influence, reputation, and even emotional support (Oh et al, 2006). Recent evidence from Romania acknowledged that both social and business networks represented the most important and reliable resource for SMEs' internationalisation (Stoian et al, 2016). Equally, evidence from Norway and Ireland showed that networks played an important role in increase speed of internationalisation (Langseth et al, 2016).…”
Section: Smes' Relationships and Export Performance: A Network-based mentioning
confidence: 99%
“…In the European Union, member states often become initial expansion markets (Wach, 2014). At present, the scope of internationalization is mostly based on knowledge, learning, and interactions that dynamically happen between partners, but also on trust necessary for further relations (Stoian, Rialp, Rialp and Jarvis, 2016). Khavul, Pérez-Nordtvedt, and Wood (2010) rightly observe that linking the activity of firms to the scope of internationalization and geographical diversity has a long history in the literature on the subject.…”
Section: The International Strategy and The Scope Of Internationalizamentioning
confidence: 99%
“…Mort and Weerawardena (2006) explain that link with evidences that fundamental and secondary networking capabilities enable identification and exploitation of market opportunities and facilitates the development of knowledge-intensive products. Stoian, Rialp, Rialp and Jarvis (2016) deepen pointing out that networks play a crucial role for knowledge creation and exchange, and frequently represent the most reliable resource at firms ' disposal, and Hashim (2015) complements by stating its role as a way to surpass external difficulties. About the Management/subsidiary autonomy factor, Gilbert and Heinecke (2014) and Gammelgaard, McDonald, Stephan, Tuselmann and Dorrenbacher (2012) agrees that increases in autonomy to an appropriate degree are highly contingent upon contextual influences, and Miozzo and Mo (2012) assigns the contingenct role to the flexibility that it brings to the firm.…”
Section: Qualitative Analysismentioning
confidence: 99%